Prototype of Learning Media for Vocational School Students Based on Project-Based Learning - Annisa (Journal of Research on Mathematics Instruction (JRMI), 2022)
The rapid development of information technology marks the 21st century, but there are still teachers who only use student worksheets as a learning resource. Project-based learning media can be used and utilized easily by teachers and students during direct teaching and learning activities. In addition, they can be used by students online as a source of student learning to increase independence, motivation, and better learning outcomes. This research aims to develop project-based learning media so students can easily understand the material and be directly involved in project activities. This study uses the ADDIE development model. The resulting product is the validity of project-based learning media on statistical material for vocational students. The first step in this research is to create a flowchart as a media flow and then interpret it using PowerPoint media. The validation of learning media results that have been carried out through the validator obtained an average score of 3.65 with a decent category for media and an average score of 3.85 for material with a very decent category.